2017
DOI: 10.1536/ihj.16-293
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Weakness Is Associated With an Increase of Left Ventricular Mass Through Excessive Blood Pressure Elevation During Exercise in Patients With Hypertension

Abstract: SummaryAutonomic imbalance in hypertension induces excessive blood pressure (BP) elevation during exercise, thereby increasing left ventricular mass (LVM). Although muscle weakness enhances autonomic imbalance by stimulating muscle sympathetic activity during exercise, it is unclear whether muscle weakness is associated with an increase of LVM in patients with hypertension. This study aimed to investigate the relationships between muscle weakness, BP elevation during exercise, and LVM in these patients. Eighty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Kamada et al . recently showed a significant negative correlation between skeletal muscle strength and BNP or left ventricular mass index (LVMI) in haemodialysis patients 29 . They proposed that potentially activated sympathetic nerve system due to weak muscle strength facilitated LVMI increase.…”
Section: Discussionmentioning
confidence: 99%
“…Kamada et al . recently showed a significant negative correlation between skeletal muscle strength and BNP or left ventricular mass index (LVMI) in haemodialysis patients 29 . They proposed that potentially activated sympathetic nerve system due to weak muscle strength facilitated LVMI increase.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research examining the relationship between eSBP and LVM has primarily found a direct association between these variables [12,16,[25][26][27][28][29][30][31][32][33][34][35][36][37][38], but this is not a universal finding [12,27,28,30,39,40]. When examining the results that do not support the association between eSBP and LVM, the participants did not habitually exercise [12,27,28,30,39,40].…”
Section: Introductionmentioning
confidence: 88%